The role of microbiota in the development and treatment of gastric cancer - Wang, Yiwen; Han, Wenjie; Wang, Na; Han, Mengzhen; Ban, Meng; Dai, Jianying; Dong, Yuesheng; Sun, Tao; Xu, Junnan (Frontiers in Oncology, 2023)
The stomach was once considered a sterile organ until the discovery of Helicobacter pylori (HP). With the application of high-throughput sequencing technology and macrogenomics, researchers have identified fungi and fivemajor bacterial phyla within the stomachs of healthy individuals. These microbial communities exert regulatory influence over various physiological functions, including energy metabolism and immune responses. HP is a well-recognized risk factor for gastric cancer, significantly altering the stomach’s native microecology. Currently, numerous studies are centered on the mechanisms by which HP contributes to gastric cancer development, primarily involving the CagA oncoprotein. However, aside from exogenous infections such as HP and EBV, certain endogenous dysbiosis can also lead to gastric cancer through multiple mechanisms. Additionally, gut microbiota and its metabolites significantly impact the development of gastric cancer. The role of microbial therapies, including diet, phages, probiotics and fecal microbiota transplantation, in treating gastric cancer should not be underestimated. This review aims to study the mechanisms involved in the roles of exogenous pathogen infection and endogenous microbiota dysbiosis in the development of gastric cancer. Also, we describe the application of microbiota therapy in the treatment and prognosis of gastric cancer.